2015
DOI: 10.1021/ja506376j
|View full text |Cite
|
Sign up to set email alerts
|

“Turn-On” Protein Fluorescence: In Situ Formation of Cyanine Dyes

Abstract: Protein reengineering of cellular retinoic acid binding protein II (CRABPII) has yielded a genetically addressable system, capable of binding a profluorophoric chromophore that results in fluorescent protein/chromophore complexes. These complexes exhibit far-red emission, with high quantum efficiencies and brightness and also exhibit excellent pH stability spanning the range of 2–11. In the course of this study, it became evident that single mutations of L121E and R59W were most effective in improving the fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
71
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 83 publications
(48 reference statements)
0
71
0
Order By: Relevance
“…4 (13), iRFP (14)] have opened new possibilities for imaging protein in deep tissue and in vivo using infrared excitation. Other interesting developments include labeling strategies relying on protein tags, such as SNAP-tag (15), PYP-tag (16), CRABPII (17), or FAPs (18-21), binding (covalently or noncovalently) an exogenously applied fluorogen. These systems present two main advantages: First, the photophysical properties of exogenous fluorogens can be tailored by molecular engineering; second, their flexibility opens new opportunities for on-demand applications wherein fluorescence is desired only at a specific time or at a given density (22).…”
mentioning
confidence: 99%
“…4 (13), iRFP (14)] have opened new possibilities for imaging protein in deep tissue and in vivo using infrared excitation. Other interesting developments include labeling strategies relying on protein tags, such as SNAP-tag (15), PYP-tag (16), CRABPII (17), or FAPs (18-21), binding (covalently or noncovalently) an exogenously applied fluorogen. These systems present two main advantages: First, the photophysical properties of exogenous fluorogens can be tailored by molecular engineering; second, their flexibility opens new opportunities for on-demand applications wherein fluorescence is desired only at a specific time or at a given density (22).…”
mentioning
confidence: 99%
“…(Wang et al, 2012) The robustness of this family of proteins, in particular hCRBPII, to mutations was the central feature that led us to use them as templates to develop rhodopsin mimics for the purpose of investigating factors that contribute to wavelength regulation. (Crist et al, 2006; Huntress et al, 2013; Lee et al, 2012; Nossoni et al, 2014; Vaezeslami et al, 2008; Vaezeslami et al, 2006; Vasileiou et al, 2009a; Vasileiou et al, 2007; Vasileiou et al, 2009b; Wang et al, 2014; Wang et al, 2012; Yapici et al, 2015) During the preparation of mutants targeted for these studies, we observed protein bands that eluted separately on ion-exchange chromatography, but nonetheless, were the same species on SDS-PAGE. This led us to the discovery of a set of hCRBPII protein mutants capable of domain swapped dimerization.…”
Section: Introductionmentioning
confidence: 96%
“…(Cowan et al, 1993; Nossoni et al, 2014; Wang et al, 2012) Both hCRBPII and other members of this family are remarkably resilient to mutation. (Berbasova et al, 2013; Berbasova et al, 2016; Crist et al, 2006; Huntress et al, 2013; Lee et al, 2012; Nossoni et al, 2014; Vaezeslami et al, 2008; Vaezeslami et al, 2006; Vasileiou et al, 2009a; Vasileiou et al, 2007; Vasileiou et al, 2009b; Wang et al, 2014; Wang et al, 2012; Yapici et al, 2015) For example more than 150 structurally stable mutants of hCRBPII have been characterized in our lab in the course of our studies of protein-chromophore interactions. (Wang et al, 2012) The robustness of this family of proteins, in particular hCRBPII, to mutations was the central feature that led us to use them as templates to develop rhodopsin mimics for the purpose of investigating factors that contribute to wavelength regulation.…”
Section: Introductionmentioning
confidence: 99%
“…In order to access Arch variants with bright NIR emission, we drew inspiration from previous demonstrations that desirable fluorescent protein properties could be obtained by expanding the limited repertoire of naturally known chromophores (Plamont et al, 2016; Tamura and Hamachi, 2014; Yapici et al, 2015). Spectral properties of the natural ATR chromophore (Figure 1 A , Compound 1) can be modulated by adding electron-withdrawing groups (Gaertner et al, 1981; Hendrickx et al, 1995) or changing the length of the conjugated π-bond system (Albeck et al, 1989; Nielsen, 2009).…”
Section: Introductionmentioning
confidence: 99%